2014
DOI: 10.1001/jamaoto.2014.1998
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Gland Cancer inBRCA-Positive Families

Abstract: We believe this is a significant observation that, when considered alongside other similarities between salivary glands and breast tissue, warrants further investigation into the nature of a possible linkage between germline BRCA mutations and salivary gland cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…We have provided the first report of a SDC patient harboring a germline BRCA1 E23fs mutation. A single previous study has shown that the prevalence of salivary carcinoma, being salivary gland carcinoma not otherwise specified and adenoid cystic carcinoma, among BRCA1-mutated probands and likely carriers is significantly higher than the background incidence rate (0.052% vs. 0.003%, p<0.001) [35]. However, possible associations between germline BRCA1/2 mutations and SDC in particular have not been previously reported.…”
Section: Discussionmentioning
confidence: 93%
“…We have provided the first report of a SDC patient harboring a germline BRCA1 E23fs mutation. A single previous study has shown that the prevalence of salivary carcinoma, being salivary gland carcinoma not otherwise specified and adenoid cystic carcinoma, among BRCA1-mutated probands and likely carriers is significantly higher than the background incidence rate (0.052% vs. 0.003%, p<0.001) [35]. However, possible associations between germline BRCA1/2 mutations and SDC in particular have not been previously reported.…”
Section: Discussionmentioning
confidence: 93%
“…Germline mutations that could account for the occurrence of both a salivary gland tumor and BC in the same woman have not been identified yet, and the literature on this topic is limited. One retrospective study including 5754 proven or likely carriers from 187 BRCA1 or BRCA2 positive pedigrees, reported three SGCs 59 . Although the authors reported an increased SGC incidence, a 95% CI was not provided.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, breast and salivary glands are known to share many morphological features, and studies have shown that both can give rise to tumors with similar morphology [ 118 , 119 ] and myoepithelial differentiation [ 120 ]. These finding can explain why breast and salivary glands clustered with epithelial and myoepithelial cells, as opposed to glandular cells.…”
Section: Discussionmentioning
confidence: 99%